2011
DOI: 10.1002/hipo.20800
|View full text |Cite
|
Sign up to set email alerts
|

Preserved hippocampal novelty responses following anterior temporal‐lobe resection that impairs familiarity but spares recollection

Abstract: Although it is well established that the integrity of the medial temporal lobe (MTL) is critical for declarative memory, the functional organization of the MTL remains a matter of intense debate. One issue that has received little consideration so far is whether the hippocampus can function normally in the presence of a lesion to perirhinal cortex that produces noticeable memory impairments. This question is intriguing as the MTL forms a hierarchical system, in which perirhinal cortex represents one of the cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 40 publications
1
20
0
Order By: Relevance
“…To explain our pattern in terms of strong memories selectively increasing hippocampal activity and weak memories selectively increasing Prc activity, one would have to assume that there is something fundamentally different about strong and weak memories that require two different neural mechanisms for each type of memory. This assumption implies two different types of memory, rather than one continuous process, which converges with other evidence suggesting functional heterogeneity in the MTL in both human and rodent models with respect to recollection and familiarity (e.g., Bowles et al, 2010; Cohn et al, 2010; Martin et al, 2011; Sauvage et al, 2008; Winters et al, 2004; Yonelinas et al, 2007). …”
Section: Discussionsupporting
confidence: 78%
“…To explain our pattern in terms of strong memories selectively increasing hippocampal activity and weak memories selectively increasing Prc activity, one would have to assume that there is something fundamentally different about strong and weak memories that require two different neural mechanisms for each type of memory. This assumption implies two different types of memory, rather than one continuous process, which converges with other evidence suggesting functional heterogeneity in the MTL in both human and rodent models with respect to recollection and familiarity (e.g., Bowles et al, 2010; Cohn et al, 2010; Martin et al, 2011; Sauvage et al, 2008; Winters et al, 2004; Yonelinas et al, 2007). …”
Section: Discussionsupporting
confidence: 78%
“…This is consistent with the hypothesized role of hippocampus in associative memory24, despite mixed findings in prior attempts to associate memory scores with structural brain measures606162 (though see refs 63 and 64). However, any simple dependence of M2 on anterior parahippocampus (as expected from prior association of perirhinal cortex with familiarity65), was not supported; nor was any simple dependence of M3 on fusiform (as expected from prior association of this region with visual priming66). This suggests that there is no simple one-to-one mapping of the memory factors onto single brain regions (or at least, onto the three ROIs considered here).…”
Section: Discussionmentioning
confidence: 83%
“…NB is a right-handed, university-educated woman whose memory deficits and lesion characteristics have previously been documented in detail elsewhere (Bowles et al, 2007;Bowles et al, 2010;Bowles et al, 2011;Martin, Bowles, Mirsattari, & Köhler, 2011 Bowles et al, 2007). Our past experimental research has revealed that NB exhibits impairments in familiarity assessment for verbal stimuli with respect to a recent experimental study exposure; these impairments contrast with entirely preserved recollection abilities.…”
Section: Participantsmentioning
confidence: 96%